Uji Aktivitas Antibakteri Ekstra Virgin Olive Oil (EVOO) Terhadap Streptococcus Agalactiae - Rahmawati, Wenny; Retnaningrum, Dwi Norma (Universitas Tribhuwana Tunggadewi, 2023)
Streptococcus agalactiae is a pathogen known to frequently cause infections in both mothers and children. It can lead to complications such as premature birth, premature rupture of membranes, postpartum infections, pneumonia, meningitis, and sepsis. Current treatment for Streptococcus agalactiae often involves antibiotics, which can contribute to antibiotic resistance. Given the increasing concern about antibiotic resistance, the development of herbal antibacterials is gaining momentum, with extra virgin olive oil (EVOO) being one such area of interest. EVOO contains oleuropein, flavonoids, and essential oils, all of which possess antibacterial properties. The objective of this research is to demonstrate the antibacterial activity of extra virgin olive oil (EVOO). The study employed a true experimental design with a post-test-only control group, using the disc diffusion method to measure bacterial inhibition zones. The results revealed the largest inhibition zone, measuring 15.9 mm, with a 3 ml dose of EVOO. The correlation test indicated a significant value of 0.000, with a coefficient of -726, suggesting that an increase in EVOO dose results in a reduction in the Streptococcus agalactiae bacterial population. Based on these findings, it can be concluded that extra virgin olive oil (EVOO) exhibits potent antibacterial activity against Streptococcus agalactiae.